Analysis of techniques for the development of english speaking skills in students of preschool level at Justo Abel Castillo Elementary School, La Concepción, Bugaba, Chiriquí, 2013 - O'Brien Sánchez, Karol Ayleen (UDELAS, 2013)
This research is based on the analysis of the techniques for the development of english speaking skill of preschool students. It contents information about the importance of the development of english speaking skill in children at early ages and which are the parts and processes of the brain that interfere during this second language acquisitional stage.